Respuestas

2012-10-10T05:05:22+02:00

                                                                 CON EL PUNTO A ( -5.2 ) Y B (4,3 ) HALLO

                                                                  LA PENDIEMTE    

Y – Y1  =  m ( X -  X1  )                                         Y2 - Y1         3  -   2              1                 1

y - 2  =   1/9   ( X - ( -5 ) )                           M =  =====  =  =====  =  =====  =  ===

Y - 2  =   1/9  ( X + 5 )                                        X2 – X1         4  - ( -5)        4  +  5             9

Y  -  2    =    1/9 X +  5 /9

Y  =  1/9 X + 5/9 + 2

Y  =  1/9 X + 23/9             SI A ESA ECUACION LE DOY EL VALOR DE X = -5        EL VALOR DE  Y = 2

 

                                        Y = 1/9 X + 23/9

                                        Y = 1/9 * -5  + 23/9

                                        Y =  - 5/9  +23/9 =  18/9 = 2

                                       Y = 2                                        por lo cual lel pumto ( -5, 2 ) pertenece a esa ecuacion